Improvements of PCR Amplification of Guanine plus Cytosine-Rich Constructs of Mycobacterium tuberculosis Gene using DMSO - Sabrina, Yunita; Lestarini, Ima Arum; Ekawanti, Ardiana; Sriasih, Made; Depamede, Sulaiman N.; Ali, Muhamad (Jurnal Kedokteran, 2012)
Vaccine research entered a new era when several useful molecular research tools were established. Instead of attenuated virulent microorganisms or killed virulent microorganisms, effective subunit vaccines were developed using recombinant DNA technology. By using the technology, selected genes of the virulent microorganisms can be amplified, cloned, expressed, and evaluated as vaccine components in challenge studies. However, a major bottleneck with the amplification of functional genes from Mycobacterium tubeculosis containing guanine plus cytosin-rich templates is often hampered by the formation of secondary structures like hairpins and higher melting temperatures. To solve this problem in this research, the amplification reaction was modified by addition of dimethyl sulfoxide (DMSO) into amplification reaction mixtures. It was found that 10% (v/v) of DMSO in the reaction mixture improved the amplification of GC-rich template of M. tuberculosis gene. This result indicating that amplification of unbalanced content of G and C deoxyribonucleotides genome could be improved using low-cost organic molecule, DMSO. Therefore, the DMSO should be widely useful as an enhancer to improve the amplification of GC rich construct from other genome. Keywords: Mycobacterium tubeculosis,vaccine, dimethyl sulfoxide, Guanine-Cytosine